Clinical, Histopathological, and Prognostic Characteristics of Patients with Prostate Cancer in Lubumbashi, Democratic Republic of Congo - Pitchou Mukaz Mbey; Olivier Mukuku; Willy Kalau Arung; Guylain Kitoko Tengu; Nasser Lubosha Amisi; Véronique Kabila Kyabu; Etienne Fwamba Koshe Odimba; François Katombe Tshilombo (Prostate Cancer)
Introduction. Prostate cancer is currently a public health problem with a frequency that varies from country to country. This study aims to describe the epidemiological, clinical, and histopathological and outcome features of prostate cancer in Lubumbashi in the Democratic Republic of Congo. Materials and Methods. This was a descriptive longitudinal study of patients diagnosed with prostate cancer at the University Clinics of Lubumbashi. The study period was 3 years (2017 to 2019). Parameters studied were age and clinical, biological (PSA level, prostatic specific antigen), histopathological, and outcome features. Results. The mean age of patients was 68.7 years (range: 47 and 90 years). The 60 to 69 age group was the most affected (43.18%). Elderly subjects (≥60 years old) represented 89.77% of the cases (n = 79). Voiding disorders were the main reason for consultation in 55.68% of the cases. The mean PSA level was 133.7 ng/ml (range: 4 and 1564.5 ng/ml) at diagnosis and 125.4 ng/ml after 3 months of follow-up (range: 0.16 and 1782.1 ng/ml). Adenocarcinoma was the predominant histological type (100%). In prognosis, 31.82% of patients had a Gleason score greater than 7 and 59.10% had a high risk at the D’Amico risk classification for Prostate Cancer. Hormone therapy was administered alone in 75% of the cases and in combination with pulpectomy in 13.64% of the cases. The 3-year overall survival was 56.82%. Conclusion. Prostate cancer is frequent and has a poor outcome in our country. The establishment of an individual screening policy would be an undeniable advantage in improving the prognosis.